Perilaku Budaya Konsumtif Petani Penggarap yang Memiliki Samben Pemelihara Sapi (Studi Masyarakat Desa Jati Kecamatan Masaran Kabupaten Sragen) - Vrisca Putri Sholekhah; Atiqa Sabardila; Rani Setiawaty (Lembaga penelitian dan pengabdian kepada Masyarakat, 2021)
Jati Village community farmers are grouped into two, namely owner farmers and tenant farmers. The main problems that will be examined in this study are (1) the general description of the tenant farmers in Jati Village, and (2) the consumptive behavior of tenant farmers in the Jati Village Community who have samben as cow raisers. The approach used in this research is qualitative with field studies. Primary data collection techniques are carried out by observation, interviews, documentation, and questionnaires. The data analysis used was descriptive analysis. Based on the results of the research, it was found that First, First, Teak community farmers, Sragen Regency cultivated approximately 2 to 3 stakes (3000-9000 meters) with a yield of IDR 5,650,000 per 1 stake (3000 meters). In addition to working on the fields, the community farmers of Jati Village, Sragen Regency, also raise cows with an income of 1 cow of Rp. 300,000, the cows are sold every 6 months to meet their lifestyle needs. Second, the consumptive behavior of tenant farmers. The people of Jati Village who have samben raising cattle tend to spend their income to improve their lifestyle. The frequency of purchasing goods by Teak community farmers to improve their lifestyle is the basic necessity of clothing in the form of clothes, pants, sandals, jackets and shoes.